Thermal degradation of poly[2-(3-aryl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] - Coskun, M; Demirelli, K; Erol, I; Ahmedzade, M (Elsevier Sci Ltd, 1998)
Thermal degradations of poly[2-(3-phenyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] [poly(PHEMA)], poly[2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] [poly(MHEMA)] and poly[2-(3-tolyl-3-methylcyclobutyl) 2-hydroxyethyl methacrylate] [poly(THEMA)] have been studied using IR spectroscopy and thermogravimetry (TG). Programmed heating was carried out at 10 degrees C/min from room temperature to 500 degrees C. All the partially degraded polymers have been examined by IR spectroscopy. Thermal degradation of poly(PHEMA) has also been studied by thermal volatilisation analysis (TVA). In degradation of poly(PHEMA) and poly(MHEMA), product identification studies were done using IR,H-1 and C-13-NMR, MS and GC-MS techniques. Depolymerization is the main reaction in thermal degradation of all three polymers up to about 300 degrees C. Intramolecular cyclisation to cyclic anhydride-type structures has been observed at temperatures above 300 degrees C. The cleaving of epoxide, ketone and diol compounds from side chains of the polymers is a common reaction for each of the polymers. (C) 1998 Elsevier Science Limited. All rights reserved.
Keywords: Methyl-Methacrylate; Copolymers